STUDI GEOKIMIA BATUAN VULKANIK PRIMER KOMPLEKS GUNUNG SINGA - GUNUNG HULU LISUNG, BOGOR - JAWA BARAT - -, Johanes Hutabarat (Fakultas Teknik Geologi Universitas Padjadjaran, 2007)
The research about study on geochemistry volcanic rocks of Gunung Singa - Gunung Hulu Lisung, Nanggung, Bogor, West Java.Samples of the Gunung Singa-Gunung Hulu Lisung were extensively analyzed for major oxides and trace elements. Compositions of geochemical samples have been plotted and are used in drawing petrogenetic inferences. volcanic rocks Gunung Singa - Gunung Hulu Lisung belong to the medium calc-alkalic to high Calc-alkalic dacite suite, and have SiO2 contents in the range of 61,34-68,55%, high Al2O3 (14,99-19,63%) and low TiO2 content and relatively high K2O (1,90-2,55%)Oxide variation diagrams for the Gunung Singa-Gunung Hulu Lisung show linear trend with much scatter. This is partially due to the fact that SiO2 makes up an increasing percentage of silicic rocks allowing less scatter in the other oxides. However, we suggest that mich of the scatter is due to mixing of variably fractionated basaltic magma with silicic magma